Guesspic Game as an Educational Game Media Knowing Living and Inanimate Objects for Children - Albertus Prana Setiawan; Bernardinus Harnadi; Erdhi Widyarto Nugroho (Soegijapranata Catholic University, 2021)
Learning to recognize understanding of the home environment, school, the benefits of helping parents and teachers in the way of educational media games. Where children in the current era love games as hobbies one of them is Guesspic games that can help children to recognize living objects and inanimate objects by coloring objects and with sounds and images - interesting animated images make children fun to play. Educational game is very interesting to develop. There are several advantages of educational games compared to conventional education methods. One of the main advantages of the educational game is the visualization of real problems. Massachusetts Institute of Technology (MIT) succeeded in proving that games are very useful for improving the logic and understanding of players about a problem through a game project called Scratch. Based on the results of previous studies, there is no doubt that educational games can support the educational process. The application of this game is designed using software or applications, namely unity. Unity is a game engine that can help make games on mobile (Smartphone) in the form of 2D games. The advantages of guesspic games can help children to recognize living objects and inanimate objects by coloring objects and with sounds and pictures - interesting animated images make children fun to play. Testing of the game to 40 users said it was easy to play, felt useful, and the child had facilities.